Characterization of alteration halos in the sediment-hosted copper deposits in the Cretaceous rocks of Neuquén basin, Argentina - Pons, María J. (2016)
Fil: Pons, María J. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología; Argentina